Online And Offline Training Of Electric Vehicle Technology For Automotive Productive Teachers At Smkn Al Mufti, Subang Regency - Ridwan Adam; Tatang Permana; Yusep Sukrawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This study aims to improve competence by providing knowledge and skills regarding maintenance and repair of electric vehicle technology (electric vehicle technology) to automotive productive teachers at Al Mufti Vocational School, Subang Regency. The training uses multiple approaches to simplify, strengthen and apply. The approach used is persuasive, collaborative and participatory. The method used is discussion, lecture, question and answer, demonstration and practice on electric cars, electric motorcycles and decomposed components. The level of achievement based on knowledge and skills carried out by post-test and pretest as well as performance tests shows the achievement of competence of 80 percent, so it is hoped that participants can transfer this electric vehicle technology to students in anticipation of the development and transition of driving technology from internal combustion engines (ICE) to electric drive.